Enantiomeric fractions of chiral polychlorinated biphenyls provide insights on biotransformation capacity of arctic biota - Warner, Nicholas A.; Norstrom, Ross J.; Wong, Charles S.; Fisk, Aaron T. (Environmental Toxicology and Chemistry, 2005)
Chiral polychlorinated biphenyls (PCBs) were measured in an arctic marine food web from the Northwater Polynya (NOW) in the Canadian Arctic to examine potential biotransformation of chiral PCB atropisomers. Organisms under investigation included pelagic zooplankton, Arctic cod (Boreogadus saida), seabirds, and ringed seals (Phoca hispida). Previous studies using achiral methods (e.g., biomagnification factors) have shown that chiral PCB congeners biomagnified in the NOW food web, but provided little information about biotransformation of PCBs except in extreme cases (i.e., high biotransformation). In this study, highly nonracemic enantiomeric fractions (EFs) were observed in several seabird species and ringed seals, but racemic EFs were found in prey (Zooplankton and fish). This suggests stereoselective and species-specific biotransformation of individual PCB stereoisomers by birds and mammals. These results are consistent with previously reported biotransformation activity of chiral organochlorine pesticides, α-hexachlorocyclohexane, and chlordane within these organisms. This study demonstrates the utility of using chiral analysis of PCBs to investigate biotransformation within biota of arctic food webs. © 2005 SETAC.